KEPRIBADIAN BIG FIVE DAN STRATEGI REGULASI EMOSI IBU ANAK ADHD (ATTENTION DEFICIT HYPERACTIVITY DISORDER) - Listyanti Widuri, Erlina (HUMANITAS (Jurnal Psikologi Indonesia), 2010)
This research was to examine a model of emotion regulation strategy on mothers of ADHD children, if big five personalities have a role on emotion regulation strategy. Quantitative analysis was carried out using AMOS 4.0 software, besides applying observation and interview. Nineteen patients of "Tumbuh Kembang Anak" section in Dr. Sardjito hospital participated in this research. The result of this research showed that: (1) Using structural equation modeling, emotion regulation strategy model that described the role of personality was accepted as model considered fit (chi square=20.268; p>0.05). (2) The result of correlation analysis between personality and emotion regulation strategy showed that the role of personality on emotion regulation strategy was not significant (y =-0,015 p>0,05). Overall, model constructed was able to explain emotion regulation strategy amounting to 2.18%.